3Rs of e-mail : risks, rights and responsibilities - Hartman, Diane B. (Crisp Pub. Menlo ParkUS, 1996)
Informs about the risks, rights and responsibilities of e-mail. Addresses user-concerns such as; loss of privacy, security, legal implications, appropriate use, effective communication and etiquette.